MEDICINES PLANNING AND PROCUREMENT MANAGEMENT AN ACADEMIC HOSPITAL IN YOGYAKARTA, INDONESIA: A QUALITATIVE STUDY - Elmiawati Latifah; Elfride Irawati Sianturi; Prasojo Pribadi; Indriyati Hadi Sulistyaningrum; Rakhmundia Aryo (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Inventory management remains a critical issue for hospital pharmacies. Thus, there is a need for pharmaceuticals to meet economic resources. Moreover, the decision to make drug requests available should be considered, and the complexity of the problem lies in the random nature of and the various constraints that must be considered in any decision. This study aimed to analyze drug management during the planning and procurement stages of medicine in a teaching hospital in Yogyakarta. The qualitative method was used to his type of research is descriptive-analytical with a case study design of one of the public, academic hospitals in the Yogyakarta area. Data collection was conducted through interviews using a content analysis approach. The analysis technique was carried out by reducing data, analyzing data, identifying themes, and extracting data interpretation with the help of NVIVO 12 software. Overall, interviews were conducted with six participants to obtain information on drug management during the planning and procurement stages in the hospital, following the standards of home pharmacy services. The stages also included budget allocation by volume of services, increasing the competence of human resources, which supports the improvement of drug management performance, implementation of e-prescribing to facilitate monitoring evaluation, and availability of complete standard operating procedures. However, the accuracy of drug planning still needs to be improved so that an integrated management information system can support optimal drug management in a teaching hospital pharmacy installation. Keywords: Drug management, drug planning, drug procurement, public academic hospital